Impact of Board Diversity on Firms’ Stability: A Study on European Firms - Nasrin, Farjana (Asian Journal of Empirical Research, 2022)
The purpose of this study is to examine the impact of board diversity of firms on firms’ stability measured by Zscore corresponds to Altman Zscore related with firms’ default risk. To test the hypothesis, a linear regression model is used on a 6-year panel data set from the year 2013 to 2018 of 180 listed firms of 10 economic sectors of 22 countries. The empirical result shows that board size has a significant negative impact; diversity of board members and board independence has a significant positive impact on firms’ stability. Beyond the theoretical implications, it has some practical implications relevant with board of directors, managers and policymakers. The findings suggest that board size with proper number of board members with having diversity can improve firms’ value. Finally, this study offers specific recommendations on how firms may improve value and stability in order to optimize their own and society's sustainable development.